Cognitive Disorders in Post-Stroke Patients - Pratiwi, Sri Hartati; Sari, Eka Afrima; Mirwanti, Ristina (Majalah Kesehatan Indonesia, 2024)
Blood circulation disorders in post-stroke patients can cause cognitive disorders. Cognitive disorders in post-stroke patients can include memory impairment, difficulty speaking, difficulty understanding things, difficulty communicating, and mood disorders. The presence of cognitive disorders in stroke patients can worsen the patient's post-stroke condition, requiring longer treatment time. This study aimed to identify the level of cognitive disorders in post-stroke patients. This research is a descriptive study to identify dementia in post-stroke patients. The sampling technique was accidental sampling for two weeks at the Neurology Polytechnic and Stroke Clinic at one of the hospitals in Bandung, totaling 83 people. The questionnaire used in this research was the Mini-Mental State Examination (MMSE). The collected data is analyzed and presented using frequency and percentage distributions. The results of this study showed that the majority of post-stroke patients (72.3%) did not experience dementia or did not experience cognitive impairment, 15.66% experienced mild cognitive impairment, and 12.04% experienced severe cognitive impairment. From the results of this study, it can be concluded that some post-stroke patients do not experience cognitive impairment, but some post-stroke patients experience severe cognitive impairment. Cognitive impairment in stroke patients can worsen the patient's condition and increase the length of treatment time. Based on the results of this research, health workers especially nurses, are expected to be able to carry out early assessments and provide particular interventions for post-stroke patients aimed at preventing the worsening of dementia and improving the patient's cognitive abilities. The intervention can be in the form of education, psychological support, and social support in the form of counseling during rehabilitation.